On the nature of the Khmilnyk Minimum of gravity - Yentin, V.A.; Gintov, O.B.; Guskov, S.I.; Mychak, S.V. (Geofizicheskiy Zhurnal, 2025)
The Khmilnyk structural and tectonic node is unique for the Ukrainian Shield. Here, a polylocal center of Precambrian acidic magmatism at the intersection of three deep faults vividly manifests in the gravitational and magnetic field Based on the interpretation of the gravity anomaly field, the geological nature of the Khmilnyk Minimum with dimensions of 25×25 km and a relative intensity of –16 mGal is due to the funnel-shaped stock of granitoids of aplite-pegmatoid and garnet-biotite composition. The magmatic activity in the central part of the stock is accompanied by deep degassing in the form of radon emanations and manifestations of uranium mineralization.